Mekanisme Trasmisi Kebijakan Moneter di Negara Berkembang - Nasution, Alya Arianti; Keisya Putri Balqis; Cindy Aulia Zalyanti; Indah Tri Sari Harahap; Maryam Batubara (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The purpose of this study is to determine the mechanism of monetary policy transmission in developing countries, the mechanism of monetary policy transmission in developing countries is a complex process that involves interactions between central banks, banks, and economic actors in the circulation of money. This article uses a literature study method, which involves collecting data by studying theories from various research-related literature and qualitative research methods. In this mechanism, the central bank regulates and controls the flow of base money as the first step, which is then transmitted through the money multiplier to circulating money according to public demand. The impact of monetary policy on broad money will affect various aspects of the economy, including inflation and real output in developing countries. An in-depth understanding of the monetary policy transmission mechanism is crucial to achieving sustainable and stable economic growth in developing countries.